The Influence of the Work Environment and Competency on Performance Through Organizational Commitments as Intervening Variables (Study on the Poverty Reduction Coordination Team Bapedda Bondowoso Regency) - Paramitha Rakhmawati; Eko Budi Satoto; Ni Nyoman Putu Martini (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2022)
This research is motivated by data on the percentage of poor people in Bondowoso Regency which is still fluctuating. Also based on the achievement of performance in the context of accelerating poverty reduction, the Sweet Tape Movement has not been optimal. The purpose of this study was to determine directly or indirectly the influence of the work environment and employee competence on employee performance through organizational commitment as an intervening variable for members of the Bondowoso Regency Poverty Reduction Coordination Team. The population of this study was 250 employees, while the number of samples was 125 people using purposive sampling technique. The analysis technique used is the Structural Equation Model (SEM) using WarpPLS 5.0. 1. the results of data analysis indicate that the test results have a significant effect on the work environment on organizational commitment of 0.001; 2. the test results have a significant effect of employee competence on organizational commitment of 0.001; 3. the test results have a significant effect of the work environment on the performance of members of 0.001; 4. the test results have a significant effect of employee competence on the performance of members of 0.001; 5. the test results have a significant effect of organizational commitment on the performance of members of 0.009; 6. The indirect effect of the work environment on the member's performance variable through the intervening variable of organizational commitment is 0.079 with a significant level of 0.010; 7. The indirect effect of the employee competence variable on the performance of members through the intervening variable of organizational commitment is 0.065 with a significant level of 0.015.